WaSH insecurity and anxiety among people who inject drugs in the Tijuana-San Diego border region - Lourdes Johanna Avelar Portillo; Alhelí Calderón-Villarreal; Daniela Abramovitz; Alicia Harvey-Vera; Susan Cassels; Carlos F. Vera; Sheryl Munoz; Arturo Tornez; Gudelia Rangel; Steffanie A. Strathdee; Georgia L. Kayser (BMC, 2024)
Abstract Background Water, sanitation, and hygiene (WaSH) insecurity increases the risk of water-related diseases. However, limited research has been conducted on psychosocial distress as it relates to WaSH insecurity, especially among people who inject drugs (PWID). We examined the relationship between WaSH insecurity and related anxiety among PWID living in different housing conditions along the US-Mexico border region. Methods From 2020-2021, a cross-sectional study was conducted among 585 people who injected drugs within the last month in Tijuana (N = 202), San Diego (N = 182), and in both Tijuana and San Diego (N = 201). Participants underwent interviewer-administered surveys related to WaSH access, substance use, and generalized anxiety disorder (GAD-7). Quasi-Poisson regressions were used to assess associations between WaSH insecurity and anxiety in the prior 6-months. Results Participants were 75% male, 42% were unhoused and 91% experienced WaSH insecurity in the prior 6-months. After adjusting for housing status, gender, and age, lack of access to basic drinking water (Adj RR: 1.28; 95% CI: 1.02-1.58), sanitation (Adj RR:1.28; 95% CI: 1.07-1.55), and a daily bath/shower (Adj RR: 1.38; 95% CI: 1.15-1.66) were associated with mild-severe anxiety. The number of WaSH insecurities was independently associated with a 20% increased risk of experiencing anxiety per every additional insecurity experienced (Adj RR: 1.20; CI: 1.12-1.27). We also found a significant interaction between gender and housing status (p = 0.003), indicating that among people experiencing sheltered/unsheltered homelessness, women had a higher risk of mild-severe anxiety compared to men (Adj RR: 1.55; 95% CI: 1.27-1.89). At the same time, among women, those who are unhoused have 37% increased risk of anxiety than those who live in stable housing conditions (Adj RR: 1.37; 95% CI: 1.01-1.89). Conclusion The lack of specific WaSH services, particularly lack of drinking water, toilets, and daily showers were associated with higher levels of anxiety among PWID in the Tijuana-San Diego border region. Women experiencing homelessness were especially vulnerable. WaSH interventions that provide safe, 24-h access may help to reduce anxiety and health risks associated with WaSH insecurity.